Measuring the effect of the anti-nerve growth factor antibodies bedinvetmab and frunevetmab on quality of life in dogs and cats with osteoarthritis using a validated health-related quality of life outcome measure: an observational real-world study - Reid, Jacqueline; Gildea, Edwina; Davies, Vinny; Thompson, Jill; Scott, Marian (Frontiers in Veterinary Science, 2024)
Dogs and cats are naturally occurring models of osteoarthritis (OA) in humans. This paper describes a real world study, using a validated health-related quality of life (HRQL) structured questionnaire instrument completed by the owner, which demonstrates the improvement in HRQL in osteoarthritic dogs and cats following treatment with the licensed anti -NGF mAbs bedinvetmab and frunevetmab respectively. Although anti-NGF mAbs have been developed for use in people, they have not yet received market authorisation and this translational study contributes to the body of evidence supporting their use in OA.